PENGENDALIAN KUALITAS UNTUK MEMINIMALISASI CACAT PRODUKSI PADA MESIN TWISTING DENGAN METODE STATISTICAL PROSES CONTROL (SPC) DI PT XYZ MAJALENGKA - Permana, Satrio Indra; Whydiantoro (Universitas Majalengka, 2021)
XYZ Majalengka is a company engaged in the printing services industry. In simple terms, maklon can be interpreted as product processing services carried out by other parties. In the process of printing, the printing company will usually make a sample of the product before the product is mass-produced. Production activities at PT. XYZ Majalengka is carried out based on the respond demand make to order strategy, namely the company carries out production activities when there is an order from the consumer. In order to maintain customer satisfaction with company performance, a quality control is needed that involves everyone, both from the company itself. Defective product problems are a major concern for the company. Apart from that, it does not rule out the possibility that the TFO (Two For One) machine will always have or defects occur during the yarn twisting production process. Therefore it is necessary to have quality control in the production process in this TFO (Two For One). Its function is clear to minimize the number of defects and improve the quality of the products produced. For this reason, quality control is carried out using the SPC (Statistical Process Control) method, which is a statistical analysis used for quality control, starting from monitoring activities, analyzing, predicting, controlling, and improving the production process and product quality through control charts. Statistical quality control using SPC (Statistical Process Control) has seven statistical tools that can be used as a tool to control quality, namely, check sheets, histograms, P control charts, Pareto diagrams, cause and effect diagrams, Scatter diagrams, and diagrams. process.